Sex, age, and family structure influence dispersal behaviour after a forced migration - Kauppi Jenni J.; Chapman Simon N.; Pettay Jenni E.; Lahdenperä Mirkka; Lummaa Virpi; Loehr John (Cambridge University Press, 2025)
Dispersal does not only mean moving from one environment to another, but can also refer to shifting from one social group to another. Individual characteristics such as sex, age and family structure might influence an individual's propensity to disperse. In this study, we use a unique dataset of an evacuated World War II Finnish population, to test how sex, age, number of siblings and birth order influence an individual's dispersal away from their own social group at a time when society was rapidly changing. We found that young women dispersed more than young men, but the difference decreased with age. This suggests that young men might benefit more from staying near a familiar social group, whereas young women could benefit more from moving elsewhere to find work or spouses. We also found that having more younger brothers increased the propensity for firstborns to disperse more than for laterborns, indicating that younger brothers might pressure firstborn individuals into leaving. However, sisters did not have the same effect as brothers. Overall, the results show that individual characteristics are important in understanding dispersal behaviour, but environmental properties such as social structure and the period of flux after World War II might upend the standard predictions concerning residence and dispersal.